Pendidikan Karakter Pada Wali Murid KB, PAUD Dan TK Mutiara Hati Desa Dibal Ngemplak Boyolali - Faqih Purnomosidi; Anniez Rachmawati Musslifah (Hakim, 2023)
Character education is very close to the word moral improvement. Character education is very important to be taught and instilled from an early age so that it is easy to teach moral meanings and morals to children. The formation of children's character can be done by instilling character values ​​consistently both when children are in the family environment, school environment, and community environment. This study aims to provide an overview to parents of students on the inculcation of moral character in their children. The method used in this study is a qualitative method and data collection by interviewing 5 informants. The results of this study are that all parents have carried out character education in educating their children to become children with good character, such as responsibility or discipline, communicative and confident.